2009
DOI: 10.1152/jn.00042.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Motor Cortical Contribution to the Anticipatory Postural Adjustments That Precede Reaching in the Cat

Abstract: We tested the hypothesis that pyramidal tract neurons (PTNs) in the motor cortex contribute to the anticipatory postural adjustments (APAs) that precede the onset of a reach in the standing cat. We recorded the discharge activity of 151 PTNs in area 4 of the pericruciate cortex during reaches of both the contralateral and the ipsilateral limbs in an instructed delay task. A total of 70/151 PTNs were identified as showing an initial short-latency period of discharge following the Go signal. Linear regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 79 publications
1
38
0
Order By: Relevance
“…Mackinnon et al (2007) demonstrated a facilitation of the muscles involved in APAs, whereas anticipatory adjustments of arm muscles were absent in patients with damage to their motor cortex (Viallet et al 1992). Moreover, animal studies have suggested that the cortex contributes to motor planning of reaching during stance (Martin and Ghez 1985;Perfiliev 2005;Perfiliev 1998;Vicario et al 1983) and the feedforward adjustments accompanying the reach (Yakovenko and Drew 2009). Thus the CNS may send a global command that specifies the planning and execution of movement and posture as one.…”
Section: Discussionmentioning
confidence: 99%
“…Mackinnon et al (2007) demonstrated a facilitation of the muscles involved in APAs, whereas anticipatory adjustments of arm muscles were absent in patients with damage to their motor cortex (Viallet et al 1992). Moreover, animal studies have suggested that the cortex contributes to motor planning of reaching during stance (Martin and Ghez 1985;Perfiliev 2005;Perfiliev 1998;Vicario et al 1983) and the feedforward adjustments accompanying the reach (Yakovenko and Drew 2009). Thus the CNS may send a global command that specifies the planning and execution of movement and posture as one.…”
Section: Discussionmentioning
confidence: 99%
“…Simple SAW can be used to transport charge carriers in semiconductor quantum well structures fabricated in thin-film GaAs=InGaAs atop LN (Rotter et al, 1999) to even form moving quantum dots as reported by Fletcher et al (2003), naturally leading to the use of such quantum dots in quantum computing by Furuta et al (2004) and even SAW-induced luminescence (Gell et al, 2006) in the quest to obtain a single-photon source. Aside from quantum applications, the ability to transport charge within semiconductors offers interesting applications in UV detectors using epitaxial ZnO thin films (Emanetoglu et al, 2004) and ZnO nanoparticles (Chivukula et al, 2010), and even solar cells (Yakovenko et al, 2009). …”
Section: A Improvement Of Analysis Techniquesmentioning
confidence: 99%
“…A forward internal model (Figure 1) is a neural mechanism that predicts (estimates) the future state of a system given the current (actual) state and the sensorimotor control signals [33–37]. The use of a forward model for coordination between posture and locomotion could operate such that the neural circuits for initiating stepping would normally be actively delayed until the APAs that generate the weight transfer from bipedal to single leg support have achieved single stance limb loading [38, 39].…”
Section: Conceptual and Theoretical Modelmentioning
confidence: 99%